2023
DOI: 10.1051/0004-6361/202243828
|View full text |Cite
|
Sign up to set email alerts
|

Modified models of radiation pressure instability applied to 10, 105, and 107 M accreting black holes

Abstract: Context. Some accreting black holes exhibit much stronger variability patterns than the usual stochastic variations. Radiation pressure instability is one of the proposed mechanisms that might account for this effect. Aims. We model luminosity changes for objects with a black hole mass of 10, 105, and 107 solar masses, using the time-dependent evolution of an accretion disk that is unstable as a result of the dominant radiation pressure. We concentrate on the outburst timescales. We explore the influence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 85 publications
1
7
0
Order By: Relevance
“…This temperature fluctuation bears resemblance to the disk instability scenario. Particularly, we noticed that the disk instability model has been proposed to explain QPEs in previous studies (Pan et al 2023;Śniegowska et al 2023) and the X-ray flares observed in ASASSN-14ko are rather similar to QPEs. Another popular model involved in explaining QPE is the star-disk collision model (Xian et al 2021;Linial & Metzger 2023), which is yet disfavored by a lower energy released by 1 order of magnitude than that observed in individual flares of ASASSN-14ko (∼10 50 erg).…”
Section: Other Scenariossupporting
confidence: 65%
“…This temperature fluctuation bears resemblance to the disk instability scenario. Particularly, we noticed that the disk instability model has been proposed to explain QPEs in previous studies (Pan et al 2023;Śniegowska et al 2023) and the X-ray flares observed in ASASSN-14ko are rather similar to QPEs. Another popular model involved in explaining QPE is the star-disk collision model (Xian et al 2021;Linial & Metzger 2023), which is yet disfavored by a lower energy released by 1 order of magnitude than that observed in individual flares of ASASSN-14ko (∼10 50 erg).…”
Section: Other Scenariossupporting
confidence: 65%
“…Several theoretical models have been proposed to explain the QPE phenomenon, including (i) accretion disk instabilities (Raj & Nixon 2021;Kaur et al 2023;Pan et al 2022;Sniegowska et al 2023); (ii) gravitational lensing of an SMBH binary (Ingram et al 2021); (iii) mass transfer onto an SMBH from one or more orbiting bodies (Zalamea et al 2010;King 2020;Chen et al 2023;King 2022King , 2023Krolik & Linial 2022;Linial & Sari 2023;Lu & Quataert 2023;Metzger et al 2022;Wang et al 2022;Zhao et al 2022);and (iv) collisions between an orbiting secondary body and the SMBH accretion disk (Suková et al 2021;Xian et al 2021;Franchini et al 2023). We focus on the latter scenario here.…”
Section: Introductionmentioning
confidence: 99%
“…The primary challenges of this phenomenon are how to construct a physical scenario to produce such short periodic eruptions (several to a dozen of hours). A number of models have been proposed, which can be roughly divided into two categories: while the first one suggests that the periodic outbursts in QPEs originate from the periodic orbital motion of a star captured by a black hole (King 2020(King , 2022Ingram et al 2021;Suková et al 2021;Xian et al 2021;Chen et al 2023;Krolik & Linial 2022;Lu & Quataert 2022;Linial & Sari 2023;Metzger et al 2022;Wang et al 2022b;Franchini et al 2023;Linial & Metzger 2023;Tagawa & Haiman 2023), another one ascribes the periodic behavior to the instability of inner accretion disk dominated by radiation pressure (Sniegowska et al 2020;Pan et al 2021Pan et al , 2022Raj & Nixon 2021;Kaur et al 2023;Śniegowska 2023). Notably, only the model of Pan et al (2022) is able to fit both the light curves and the phase-resolved X-ray spectra simultaneously during outbursts in GSN 069.…”
Section: Introductionmentioning
confidence: 99%
“…The main difficulty of this disk instability model for QPEs is the viscous timescale of the thin accretion disk being significantly larger than the observed periods of QPEs (e.g., Pan et al 2021Pan et al , 2022. It was suggested that the viscous timescale of a disk driven predominantly by magnetic outflows can be substantially shortened (Cao & Spruit 2013;Li & Begelman 2014;Li & Cao 2019;Feng & Cao 2021;Kaur et al 2023;Pan et al 2022;Śniegowska 2023). Pan et al (2022) constructed an instability model of the disk with magnetically driven outflows for the QPEs of GSN 069, and both its light curve and phased-resolved X-ray spectra have been fitted by their model fairly well.…”
Section: Introductionmentioning
confidence: 99%